Mudanças ambientais no Cerrado Pé-de-Gigante (Santa Rita do Passa Quatro-SP): um olhar para mudanças temporais na comunidade herbáceo-subarbustiva e para o córrego Pauliceia - Silva, Márcia Cristina Martins da (Universidade Federal de São Carlos, 2022)
There are several changes that time brings to the environment. This study sought to elucidate these changes in the flora of a cerrado area (Brazilian Savanna) in the Sao Paulo state, the Gleba Cerrado Pé-de-Gigante (Vassununga State Park) after more than two decades. The focus was the composition and structure of the posterior vegetation of the subarbus vegetation, repeating a study carried out 24-year ago in the same location and with the same methods. In this dissertation, the first chapter deals with this survey, carried out in 2021, in 324 0,5 x 0,5 m plots. Using PERMANOVA analysis and generalized mixed-effects models we saw differences in composition and we point out the woody encroachment as one of the factors of these changes. The chapter also provides a mapping and updating of the locations of the sources of the Paulicéia Stream, which rises entirely in the same study area. After more than 20 years, then, a reduction in the number of springs in relation to the topographic facts in the literature, in addition to the fact that these were impacted, above all, the presence of exotic invasive species of the fauna (Sus scrofa), although its location is a protected area. In the second chapter, we approach the quality and integrity of this stream, in order to determine the conditions of its waters. Habitat Integrity Index and Biotic Index, using benthic macroinvertebrates, were applied at seven collection sites in the dry season. We verified in a principal components analysis (PCA) the water abiotics that can influence the composition of the macroinvertebrate community and then a linear mixed model was applied to the result, where we obtained the expected result that more intact the habitat, more diverse the aquatic community. Finally, in the third chapter, we also carried out a systematic search in the literature and in virtual herbaria about the entire flora of the Cerrado-Pé-de-Gigante Gleba. The results can generate an updated list of species recorded in the area, which are compared with other nearby protected areas, where we were able to conclude that - although impacted - this Cerrado remnant is an important and rich fragment, which should receive attention for management and conservation actions.
Environmental changes in the Cerrado Pé-de-Gigante (Santa Rita do Passa Quatro-SP): a view at temporal changes in the herbaceous-subshrub community and the Pauliceia stream
Keywords: Cerrado; Flora Herbáceo-subarbustiva; Macroinvertebrados Bentônicos; Nascentes; Área Protegida; Brazilian Savannah; Subshrub-herb; Benthic Macroinvertebrates; Springs; Protected Area; CIENCIAS BIOLOGICAS::ECOLOGIA